Membangun Koneksi Sosial dan Emosional pada Anak Usia Dini - Sri Jumiaty Permatasari (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Early childhood education (PAUD) has a very important role in building the foundation of children's social and emotional development. This study aims to examine various approaches in building social and emotional connections in early childhood based on existing literature studies. Various factors, such as teacher and peer interactions, the role of parents, and a supportive environment, have a significant influence on children's social and emotional development. This study concludes that an inclusive and participatory approach to learning can encourage children to build positive relationships with others, manage their emotions, and develop empathy. In addition, character education and learning based on social experiences can improve children's ability to adapt to various social situations. By understanding the importance of social and emotional aspects, it is hoped that learning in PAUD can be more holistic and oriented towards balanced development between cognitive, social, and emotional aspects.